Implementation parallel firewall at Cosmopoint Melaka to improve performance - Noh, Nalizawati (2017)
Nowadays, the concept of having isolated LAN for an institution network is no longer relevant. This thing same goes with the Cosmopoint College Melaka. Internet became is an essential part and plays an important role in institution. So, firewall became is an important components in improving network security. It’s can examine all the in and out traffic of the network. This dissertation focused on the study about relationship between security and network performance. Its will demonstrate the concept of firewall, function of firewall in the network, the types of firewall and its importance in the network. Besides that, this dissertation will discuss the effect brings to network performance while implementing the firewall. Riverbed Modeler Academic Edition is used as a tool to perform simulation and analysis data. In this paper also discuss about parallel firewall in order to limit the network delay.